Pengaruh latihan Rondo terhadap keterampilan menyerang pada tim MAN 1 Kota Gorontalo - Diuli, Mohamad Reza Pratama (Universitas Negeri Gorontalo, 2025)
The objective of this study is to determine the effect of Rondo training on futsal attacking skills. The research employs an experimental method with a sample of 10 players from MAN 1 Kota Gorontalo. Data collection was conducted using Game Situation tests, analyzed through both descriptive and inferential statistical methods to test the research hypotheses. Based on the t-test data analysis for attacking skills, the observed value (-4.177) with a significance level of 0.002 0.05 indicates that Rondo training has an effect on futsal attacking skills. These results show a significant influence of Rondo training on the attacking skills of the MAN 1 Kota Gorontalo futsal team.